Clinical and Magnetic Resonance Imaging Characteristics of Pediatric Acute Disseminating Encephalomyelitis With and Without Antibodies to Myelin Oligodendrocyte Glycoprotein - Lei, Meifang; Cui, Yaqiong; Dong, Zhaoying; Zhi, Xiufang; Shu, Jianbo; Cai, Chunquan; Li, Dong (Frontiers in Pediatrics, 2022)
Background: MOG-IgG associated disorders (MOGAD) has been considered as a new inflammatory disease entity of the central nervous system (CNS) and has heterogeneous clinical and imaging presentations. ADEM (acute disseminated encephalomyelitis) is one of the most important phenotypes. Our research aimed to compare the clinical and MRI (magnetic resonance imaging) characteristics of ADEM with or without MOG-IgG in paediatric acquired demyelinating syndromes (ADSs). Methods and Results: We retrospectively reviewed the clinical characteristics, MRI features and outcomes of paediatric ADSs patients from March 2017 to February 2021 in our centre. MOG-IgG was analysed by transfected cell-based assay (CBA). Among 46 children with ADEM, 21 children (11 girls and 10 boys) were positive for MOG-IgG. Headache, fever, vomiting, vertigo, ataxia, and decreased muscle strength were common in all enrolled children. No significant difference existed in demographic characteristics, symptoms at initial episode or laboratory CSF finding between children with MOG-IgG and children without MOG-IgG. For children with MOG-IgG seropositive ADEM, cerebral MRI showed widespread, poorly demarcated bilateral lesions, especially in cortical and subcortical white matter and spinal MRI often showed lesions spanning more than three segments. The significant difference in MRI features between the two groups was the presence of lesions in the thalamus and cortical area (P<0.05). Most children in both groups showed clinical improvement one week after immunotherapy and achieved recovery during their hospital stay. Three children with MOG-IgG and four children without MOG-IgG had one or more relapsing courses with median interattack intervals of 4 (range:1 to 7) months and 10 (range: 1-24) months, respectively. New clinical symptoms and lesions on cerebral and spinal MRI were found during relapsing courses in two groups. No recurrences were recorded 6 to 51 months after each patient’s last episode. Conclusions: There was no significant difference in clinical characteristics between ADEM children with MOG-IgG and ADEM children without MOG-IgG. For children with MOG-IgG seropositive ADEM, cerebral MRI showed large, bilateral lesions and spinal MRI often showed lesions spanning more than three segments. Children achieved a favourable outcome regardless of MOG-IgG serostatus.